A Sımple Orthodontıc Approach In Late Permanent Dentıtıon For Class Iı/1 Cases: Removable Herbst Applıance - Eray Erdoğan (Turkish Journal of Orthodontics, 1996)

(untitled)
The disadvantages of fixed Herbst appliance, such as hgiene problems, limitations of mandibular functional movements, etc., leads certain authors to design a new removable appliance having same mechanic principals. The telescopic force component of this new appliance placed on the thermoplastic upper and lower retention plates allows the correction of class II problems by advancing the mandible. In this article, an adolescent case who refused the classical orthodontic approach (headgear, edge wise appliance and intermaxillary elastics) to correct his severe skeletal and dental class II malocclusion; treated with the removable Herbst appliance in presented and the dentofacial effects of this appliance are discussed. After an experimental phase 6 months, the positive results of this therapy were observed and the treatment was completed with the same mechanic to solve the major orthodontic problem of the present case. The records taken after 14 months of active treatment phase show the signifiant improvement of postero-divergent concave soft tissue profile to orthognathic profile by the dental and skeletal retraction of the maxilla and the forward displacement of the mandible. This appliance being simpler compared to the other activators and fixed appliances had increased the patient motivation and helped the achievement of the orthodontic treatment.